The ceramic sequence of Tikal - Culbert, T. Patrick; Kosakowsky, Laura J. (University of Pennsylvania Museum of Archaeology and Anthropology, 2019)
The two volumes of the central Tikal ceramic reports (Tikal Reports 25A and 25B) present the information gathered from the analysis of all ceramics recovered by the University of Pennsylvania research project at Tikal between 1956 and 1970. Tikal Report 25A (Culbert 1993) contains illustrations and brief descriptive captions for all whole vessels recovered from burials, caches, and problematical deposits. Because Tikal Report 25A illustrates the often-spectacular decorated vessels from major burials, it is of the most general interest for comparative purposes.This volume, Tikal Report 25B, presents the Tikal sequence of nine ceramic complexes (the analysis of the small sample of Postclassic Caban ceramics was not completed), describes the ceramics from each complex, presents the data for all counted lots, and illustrates the material from sherd collections. It is a specialist volume, primarily of interest to those actively involved in research with Maya ceramics. The material is complemented by data in the Tikal Reports devoted to excavations and by the analysis of nonceramic artifactual material in Tikal Reports 27A and 27B (Moholy-Nagy and Coe 2008; Moholy-Nagy 2003).